2013
DOI: 10.1007/s00405-013-2608-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for T1a glottic cancer: the influence of smoking cessation and fractionation schedule of radiotherapy

Abstract: The objective of the presented study is to report on retrospectively collected data on long-term outcome and toxicity and prospective assessment of quality of life (QoL) and Voice-Handicap Index (VHI) of patients with T1a glottic cancer treated with radiotherapy. Between 1985 and 2011, 549 patients were treated. Endpoints were local control (LC), toxicity, QoL and VHI. After a median follow-up of 93 months, the actuarial rates of LC were 91, and 90 % at 5- and 10-years, respectively. Continuing smoking (p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…No articles were excluded based on language. One study was excluded because the results were described in another study . The study that included the largest study population of the 2 was included for further analysis .…”
Section: Resultsmentioning
confidence: 99%
“…No articles were excluded based on language. One study was excluded because the results were described in another study . The study that included the largest study population of the 2 was included for further analysis .…”
Section: Resultsmentioning
confidence: 99%
“…6 Smoking cessation in the general population is known to improve health outcomes and create significant reductions in health expenditures. 6 , 7 Whereas many studies found that smoking cessation after a cancer diagnosis can improve survival, 8 , 9 , 10 , 11 , 12 , 13 to our knowledge, there have been no evaluations of the association between continued smoking among patients with cancer and the costs of cancer treatment. Understanding the financial effects of smoking among patients with cancer is needed to develop value-based approaches that could lead to improved cancer treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…18 Al-Mamgani et al retrospectively demonstrated that patients with early stage glottis cancer who continued smoking after radiotherapy had significantly poor local control and low voice quality; however, the acute adverse effects during radiotherapy were not addressed. 19 Peppone et al retrospectively demonstrated association between smoking and increased symptom burden, during and following the treatments for cancer. 20 Hoff et al prospectively showed that heavy smokers had significantly reduced probability of locoregional control, disease-specific survival, and OS, compared to non-smoking patients, while not addressing the acute adverse effects during radiotherapy.…”
Section: Discussionmentioning
confidence: 99%